Examining the Association Between Socioeconomic Status and Invasive Colorectal Cancer Incidence and Mortality in California - Steinbrecher, Astrid (Cancer Epidemiol Biomarkers Prev, 2012)
BACKGROUND: Colorectal cancer (CRC) incidence and mortality rates vary across race/ethnicity. Socioeconomic status (SES) also influences CRC rates; however, these associations might be inconsistent across racial/ethnic groups and tumor subsite. We examined associations between area-level SES and CRC incidence and mortality in a population-based registry study of non-Hispanic Whites, African Americans, Hispanics, and Asians/Pacific Islanders from California. METHODS: Data on 52,608 incident CRC cases (1998–2002) and 14,515 CRC deaths (1999–2001) aged ≥50 years were obtained from the California Cancer Registry. Based on 2000 U.S. Census data, each cancer case and death was assigned a multidimensional census tract-level SES index. SES-specific quintiles of CRC incidence and mortality rates, incidence rate ratios (IRR) and mortality rate ratios, and 95% confidence intervals (CI) were estimated. Analyses were stratified by anatomical site, including left- versus right-sided tumors, race/ethnicity, and stage of disease. RESULTS: Overall CRC incidence and SES did not show a clear association, yet patterns of associations varied across tumor subsite and race/ethnicity. Positive associations between SES and CRC incidence were found in Hispanics [SES Q5 v. Q1: IRR = 1.54, CI = 1.39–1.69], irrespective of the subsite. For Whites [SES Q5 v. Q1: IRR = 0.80, CI = 0.77–0.83], and African Americans [SES Q5 v. Q1: IRR = 0.83, CI = 0.70–0.97] inverse associations were observed, predominantly for left-sided tumors. Mortality rates declined with increasing SES in Whites, whereas in Hispanics mortality rates significantly increased with SES. CONCLUSIONS: Our findings show that SES differences in CRC incidence and mortality vary considerably across anatomical subsite and race/ethnicity. IMPACT: Studies combining area- and individual-level SES information are warranted.